A Case of Septic Arthritis of the Shoulder Due to Yersinia enterocolitica with Review of the Literature. (2nd August 2014) - Chan, Justin; Gandhi, Rajesh Tim
Abstract: Yersinia enterocolitica infection rarely can cause extra-intestinal infections. We present a case of septic arthritis of the shoulder due to this organism in an elderly man with liver and cardiac disease. We review previously published cases of Y. enterocolitica septic arthritis, and discuss risk factors and management.